The injection of rice bran oil to avian egg: focus on carotenoids content of liver and brain in embryonic period - Sadighara Parisa; Araghi Atefeh; Sayrafi Reza; Moghaddam Sepehri (Shahrekord University of Medical Sciences, 2015)
Introduction: The brain and liver are highly vulnerable to oxidative stress in embryo developmental periods. The levels of antioxidant in these tissues are correlated with the mother's nutrition during pregnancy. The present study was conducted to assess the level of carotenoids in liver and brain following the injection of Rice Bran Oil (RBO) to the chicken embryo. Methods: The eggs were divided into three groups (n=10, for each group). 0.1 cc of RBO was injected into the chorioallantoic membrane and into the egg yolk on the day 4 of incubation. The experiment was terminated on the day 20 of incubation, then, the liver and brain sample tissues were collected. The carotenoids level was measured and compared in the groups. Results: The levels of carotenoids of the eggs yolks in which RBO were injected in them were 0.31±0.08 and 1.2±0.08 (μg/g tissue) in brain and liver, respectively. These changes were significant as compared with control group (P<0.05). Conclusion: RBO exposed embryo significantly increased carotenoids level of liver and brain. Therefore, the result of this study confirms health benefit of RBO consumption during embryonic development.